A influência da dança na percepção de estruturas rítmicas monotônicas em adolescentes surdos - Mauerberg-DeCastro, E. [UNESP]; Moraes, R. (Desafio Singular, Lda, 2013)
Dance activities were administered to a group of deaf adolescents via visual and auditory stimuli in order to improve their perceptions of monotonic rhythmic structures. Status of psychomotor development was also assessed before and after participation in the program. Twenty deaf adolescents (ages between 12 and 13 years) were divided into two groups, experimental (EG) and control (CG). Before and after participating in the program for 26 weeks, participants were evaluated in rhythmical tasks adapted from the classical test of M. Stambak. The tasks included the perception of drum beats, actually viewed hit movements, or heard via a sound amplifier. Psychomotor tests were administered only to the EG. The period of practice with dance activities changed the individuals' performance in the monotonic rhythmic test. Also, the success rate improved in both, visual and auditory input tasks. Individuals in the CG showed no changes in performance. For the EG, in the post-test, the status of psychomotor development was six months below the target age of the tests (i.e., 11 years). Findings suggested that dance activities can change deaf individuals' auditory perception of rhythmic structures. Participation in such a program can also positively affect psychomotor development. © FTCD/FIP-MOC.
Effects of dance on perception of monotonic rhythmical stimuli in deaf adolescents
Keywords: Auditory perception; Dance; Deafness; Rhythm